RELIGIOUS ISSUES IN THE 1883 KRAKATOA DISASTER AND TSUNAMI IN COASTAL BANTEN 2018: A COMPARATIVE STUDY (International Conference on Social and Islamic Studies, 2022)
The 1883 Krakatau eruption and the 2018 tsunami that hit the coast of Banten and Lampung are among the most memorable disasters in Indonesian history. One occurred during the colonial period when technology had not yet reached the sophistication it has today, and the other when technology was very advanced. This research aimed to see what religious issues developed in the 1883 Krakatau eruption and the 2018 tsunami. This research uses the historical method of heuristic, criticism, interpretation, and historiography. Data collection was done through a literature study. The past and present are connected through three approaches, namely genetic, historical parallelism, and comparative. The approach used in this research compares the similarities and differences related to religious issues related to disasters in two different periods and events. Religious issues, in view of those who believe in them, play an important role in the causes and effects of disasters. Religious issues that can be read in these two events range from forms of religious fanaticism to religious sentiment. Understanding religious issues related to disasters from an emic perspective will help plan disaster mitigation appropriately amidst the short memories of communities in disaster-prone areas.